ANALISIS SIKAP MASYARAKAT TERHADAP KUNJUNGAN WISATAWAN ASING KE PANTAI PARANGTRITIS YOGYAKARTA - Adriana Yustina Nora (Journal of Tourism and Economic, 2018)
This study aims to determine the Cognitive, Affective, and Conative attitudes of the communities around the tourist sites of Parangtritis beach in Yogyakarta to visit foreign tourists. Parangtritis is one of the most famous tourist attractions in the province of Yogyakarta Special Region is a tourist destination that is most frequently visited by foreign tourists. The attraction of Parangtritis beach is the charm of Parangtritis beach in the evening at sunset which is often used as a moment for tourists, the temple on the hill located on the east of the beach, interesting attractions of All Terrain Vehicle (ATV) and kite festivals at other tourist locations located around Parangtritis beach. Research data was collected from the community using a questionnaire. From the results of the study showed that the regression coefficient on Cognitive variables (X1) is 0.016 positive so that it can be said that Cognitive variables (X1) have a positive effect on the attitude of the community. While the Affective variable (X2) is -0.252 which is negative, which means it has a negative effect on the attitude of the community. Likewise with the Conative variable (X3) of 0.055 positive value also has a positive effect on the attitude of society.Keywords: Parangtritis, Cognitive, Affective, Conative, Community Attitudes